SWOT-AHP-Based strategies for improving corn productivity and export sustainability in Gorontalo, Indonesia - Indriana Indriana; Sjahril Botutihe; Jolanda CE Lamaega (Journal of Agricultural Socio-Economics (JASE), 2026)
Corn is a strategic commodity for Gorontalo Province because it supports food security, farmer income, regional agribusiness development, and export-oriented agricultural competitiveness. However, corn productivity and export sustainability in the region are still constrained by production risks, limited post-harvest facilities, weak institutional support, and market access challenges. This study aims to formulate and prioritize strategies for improving corn productivity and export sustainability in Gorontalo Province using an integrated SWOT-AHP approach. Data were collected through surveys of 98 corn farmers, stakeholder interviews, field observations, and expert judgment. SWOT analysis was used to identify internal and external strategic factors related to cultivation, post-harvest, distribution, and institutional aspects, while AHP was applied to determine the priority weights of criteria, sub-criteria, and alternative strategies. The SWOT results show that weaknesses were more dominant than strengths, and threats were more dominant than opportunities, placing corn farming in the WT quadrant with coordinates of X = −0.53 and Y = −0.64. This indicates that the appropriate strategic direction is a defensive strategy, emphasizing the minimization of internal weaknesses and the anticipation of external threats. The AHP results show that production was the highest priority criterion (0.39), followed by post-harvest (0.31), institutional aspects (0.22), and distribution (0.08). At the sub-criteria level, productivity improvement obtained the highest priority weight (0.67). The main alternative strategy was pest and disease control (0.46), followed by the addition of harvest and post-harvest facilities (0.18) and seed quality improvement (0.16). These findings indicate that strategies to improve corn productivity and export sustainability in Gorontalo should prioritize risk management in production, post-harvest infrastructure improvements, and support for quality seed. The study provides practical guidance for local government, extension officers, farmer groups, and agribusiness actors in strengthening the competitiveness of Gorontalo corn.